MEMBANGUN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR DALAM MENYAMBUT PENDIDIKAN BERKUALITAS - Imelda Meyvita; Anisah Nur Azizah; Jihan Alya; Yulinar Maharani Agetta; Zulfadewina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine various obstacles faced by elementary school teachers in their efforts to strengthen their professional competencies to support the achievement of quality education. Teachers' professional competencies play a crucial role in supporting the improvement of education quality, although many teachers still face difficulties in meeting the demands of competencies relevant to the dynamics of the times. Several factors contributing to this situation include limitations in developing 21st-century skills, such as critical thinking, creativity, collaboration, communication, and digital literacy. To address these challenges, strengthening professional competencies through continuous training, integrating technology into the learning process, and collaboration among educators in learning communities are appropriate approaches. This study uses literature review and empirical research methods to examine in depth the obstacles and strategies in teacher competency development. The results of this study are expected to provide input for efforts to improve the quality of education in the future through strengthening teacher professionalism.